Modeling seismic hazard and landslide occurrence probabilities in northwestern Yunnan, China: exploring complex fault systems with multi-segment rupturing in a block rotational tectonic zone - J. Cheng; C. Xu; X. Xu; S. Zhang; P. Zhu (Natural Hazards and Earth System Sciences)
The northwestern Yunnan region, located on the southeastern edge of the Tibetan Plateau, is characterized by a combination of ductile flow of the lower crust with low shear-wave velocity and gravitational collapse, giving rise to a complex network of active faults. This presents significant seismic hazards, particularly due to the potential for multi-segment ruptures and resulting landslides. This article presents a new seismic hazard model for the northwestern Yunnan region, incorporating recent findings on fault geometry and slip rates along with historical seismicity rates to assess multi-segment rupturing risks. Among the four potential multi-segment rupture combination models examined, Model 1, characterized by multi-segment rupture combinations on single faults, particularly fracturing the Zhongdian fault, is proposed as the most suitable for the northwestern Yunnan region, given that the non-mainshock slip ratios on fault segments are all below the 30 %–40 % threshold, as supported by the agreement of modeled seismicity rates with fault slip rates. Our analysis demonstrates that the peak ground acceleration (PGA) for a mean return period of 475 years, which is calculated with the developed probabilistic seismic hazard model, has a strong correlation with the spatial distribution of the faults. On average, these values are higher than the PGA given by the China Seismic Ground Motion Parameters Zonation Map. Furthermore, we utilized PGA values with the Bayesian probability method and a machine learning model to predict landslide occurrence probabilities as a function of our PGA distribution map. Our findings underscore that the observed combinations of multi-segment ruptures and their associated behaviors were in alignment with the small block rotation triggered by the gravitational collapse of the Tibetan Plateau. This result highlights the intricate interplay between multi-segment rupturing hazards and regional geological dynamics while also providing valuable guidance for disaster preparedness efforts.